Kemampuan Ekstrak Buah Okra Hijau (Abelmoschus Esculentus) 100% dalam Membentuk Kedalaman Mikroporositas Enamel Gigi - Shabrina Faizzatul Uula (Fakultas Kedokteran Gigi, 2026)
Introduction: Management of dental lesions should consider both esthetic aspects and restoration strength. Composite resin is a tooth-colored restorative material that bonds micromechanically to enamel through the formation of resin tags within enamel microporosities produced by acid etching. Thirty-seven percent phosphoric acid (H₃PO₄) is considered the gold standard etching agent because it produces optimal enamel microporosity depth; however, it has been reported to damage oral epithelial cells. This condition has encouraged the development of natural materials as more biocompatible alternative etching agents. Green okra (Abelmoschus esculentus) contains various organic acids that may induce enamel demineralization and antioxidant compounds expected to minimize cellular damage. Objective: This study aimed to analyze the ability of 100% green okra extract to form enamel microporosities and to compare the resulting microporosity depth with that produced by 37% H₃PO₄. Methods: This laboratory experimental study with a post-test only control group design used 10 maxillary first premolar teeth divided into two groups. Group I was etched using 37% H₃PO₄ for 20 seconds, while Group II was etched using 100% green okra extract for 20 seconds. Samples were examined using a scanning electron microscope (SEM) at magnifications ranging from 4000× to 10000×. Microporosity depth was measured using the Phenom User Interface. Data were analyzed using Shapiro–Wilk, Levene’s test, and Independent T-test. Results: The mean enamel microporosity depth in the 37% H₃PO₄ group was 19.73 µm, while the 100% green okra extract group showed a mean depth of 25.31 µm. Independent T-test analysis showed no statistically significant difference between the two groups (p = 0.176). Therefore, 100% green okra extract demonstrated a comparable ability to form enamel microporosities to that of 37% H₃PO₄.
Finalisasi 21 Juli 2026_Yudi
Keywords: enamel microporosity; green okra extract; phosphoric acid; etching agent; SEM.